PENGARUH LEADER- MEMBER EXCHANGE (LMX) DAN PERCIEVED ORGANIZATIONAL SUPPORT (POS) TERHADAP KOMITMEN AFEKTIF (Studi Kasus Pada Karyawan Rumah Sakit Mekar Sari Bekasi) - Harthantyo, Yogi; Rahardjo, Mudji (Faculty of Economics and Business Diponegoro University, 2017)
This research is aim to analyze the influence of member exchange (LMX) and perceived organizational support (POS) against affective commitment through employee of Mekarsari Hospital in Bekasi. The utilization of Affective Commitment can be an excuse for the hospital in improving the quality of health services that provided. The population used in this research is the imployees of Mekarsari Hospital in bekasi according to the characteristics specified. This research method is using multiple regression analysis technique by taking samples with total sampling method which the samples used were 120 respondents. Data obtained from the questionnaire that were distributed directly to employess then processed and analyzed using SPSS program. The results showed that the independent variables in this study, Leader- Member Exchange (LMX) has a positive and significant impact on Affective Commitment with the value of Standardization Coefficient in the amount of Î² 0, 404. Furthermore, the Perceived Organizational Support (POS) variable has positive and significant impact on affective commitment employees with a value of Standardized Coefficients in the amount of Î² 0, 263.